Effectiveness of a Cloud Learning Management System in Developing the Digital Transformation Skills of Blind Graduate Students - Amr El Koshiry; Entesar Eliwa; Tarek Abd El-Hafeez; Mohamed Abd Allah Tony (Societies)
Digital transformation has become a critical aspect of modern education, necessitating the development of digital skills among all students, including those with disabilities. Among these, blind students face unique challenges in acquiring the digital competencies needed for academic success and professional integration. This study aimed to enhance the digital transformation skills of blind postgraduate students by evaluating the effectiveness of a cloud-based learning management system, Moodle Cloud. Using a mixed methods approach, we combined descriptive and quasi-experimental designs to assess the impact of the intervention. The sample included 20 blind graduate students from Beni Suef University, equally divided into experimental and control groups. Pre- and post-assessments measured participants’ digital transformation skills through achievement tests and performance evaluations. The findings indicated significant improvements in the experimental group, with higher scores in both the achievement tests and performance assessments compared to the control group. The results suggest that the cloud-based learning management system played a vital role in enhancing digital skills, and no significant differences were found between remote and in-person applications of the intervention. The study emphasizes the importance of incorporating modern digital technologies into the education of blind students, aligning with Egypt’s Vision 2030 plan and ongoing educational reforms.